EFFICACY OF A WEIGHT MANAGEMENT PROGRAMME ON CLINICAL METABOLIC PARAMETERS: A SINGLE-CENTRE EXPERIENCE IN MALAYSIA - Mohamad, Aimi Fadilah; Ismail, Zaliha; Hatta, Sharifah Faradila Wan Muhamad; Warman, Nuraini Eddy; Zainordin, Nur Aisyah; Shah, Fatimah Zaherah Mohamed; Ghani, Rohana Abdul (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Weight management clinics aim to reduce obesity-related effects particularly the metabolic complications. The UiTM weight management clinic comprises a 7-visit programme over a 1-year period involving various specialties such as primary care physicians, endocrinologist, nutritionist, psychologist, and rehabilitation medicine. Each provides different aspects of obesity management focusing predominantly on lifestyle modifications. The impact of this programme on clinical metabolic parameters such as weight, waist, hip, and neck circumferences were assessed. METHODOLOGY This is a retrospective analysis involving 59 patients who successfully completed the weight management programme in UiTM between June 2018 and December 2020. Completion of the programme was defined as attendance to all 7 visits. All data were acquired through patients’ medical records. Changes in weight, waist circumference (WC), hip circumference (HC) and neck circumference (NC) at baseline, 6 months, and 12 months were analyzed. Paired t-test analysis was performed using SPSS version 22. RESULTS 59 patients were evaluated. Baseline weight was 123.3 ± 26.0 kg. Weight change at 6 months was -3.74 ± 7.9 kg and at 12 months was -4.37 ± 11.7 kg. The mean difference in weight between 6 and 12 months was statistically significant with p=0.006. Significant differences were also seen in the other parameters as well. WC change at 6 months was -3.49 ± 7.8 cm and -4.26 ± 7.9 cm at 12 months (p<0.001). Change in HC was -2.46 ± 5.8 cm and -3.42 ± 7.7 cm at 6 months and 12 months respectively (p=0.001). Lastly, change in NC at 6 months was -0.75 ± 2.2 cm and -0.63 ± 2.1 cm (p=0.022). CONCLUSION There were significant changes in weight and other clinical metabolic parameters with personalised lifestyle changes given through a structured weight management programme. These changes can be seen as early as 6 months and extends to 12 months. This correlates with current evidence that lifestyle changes require a minimum of 6 months’ duration to achieve meaningful metabolic results.